Hermeneutika Hadis tentang “Hidupkan Saya Bersama Orang Miskin” (Analisis Kualitas dan Sharh Hadis) - Khairil Ikhsan Siregar (Hayula: Indonesian Journal of Multidisciplinary Islamic Studies, 2021)
Abstract This article discusses the text of the hadith: "Hadith Turns Me With the Poor People" from the side of the hadiths and understands the hadith using the hermeneutic theory approach in the hadith. This research is research based on the library (library research). The approach used is descriptive qualitative which aims to describe or describe the existing or actual facts of the object under study. The results of this study indicate that the quality of the hadiths from the narrative path is dha'if (weak) based on the comments of hadith critics scholars in the books of al-jarh wa al-ta'dil and the hadith scholars conclusion that hadith dha'īf is not including false it can be part of moralities. The real method of hermeneutics to explain hadith texts contributes to enriching the explanation of the explanation hadiths, or sharh hadiths, so the meaning of the hadith text is that the words of miskin( poverty), al-masakin(needy) mean humility, reverence, and humbleness. And the meaning of hadith has been strengthened by presenting other hadiths as witnesses or i'tibar(regard). Keywords: hermeneutics, hadith, poor. Abstrak Artikel ini membahas teks hadits: “Hadits Hidupkan Saya Bersama Orang Miskin” dari sisi sanad/jalur periwayatan hadistnya dan memahami hadits dengan pendekatan teori hermeneutika dalam hadits. Penelitian ini adalah penelitian kualitatif berdasarkan perpustakaan (library research). Pendekatan yang digunakan adalah deskriptif kualitatif yang bertujuan untuk menggambarkan atau menggambarkan kenyataan yang ada atau kenyataan aktual dari objek yang diteliti. Hasil penelitian ini menunjukkan bahwa kulitas hadist dari jalur periwayatnya dha’if atau lemah berdasarkan komentar ulama kritikus hadits dalam kitab-kitab al-Jarh wa al-Ta’dil dan simpulan ulama hadits bahwa hadits dha’if yang bukan hadits palsu dapat dijadikan bagian dari fadha’il al-a’mal. Sesungguhnya metode hermeneutika untuk menjelaskan teks-teks hdits memberi kontribusi memperkaya upaya penjelasan/ syarh hadits/ teks hadits maka makna teks hadits bahwa ucapan kemiskinan / miskinan , al-masakin maknanya adalah kerendahan hati, ke_khusyu’-an dan tawadhu’. Dan makna hadits telah dikuatkan dengan menghadirkan hadits-hadits lain sebagai syaksi/i’tibar. Kata Kunci: hermeneutika, hadits, miskin